Hospitalização de Pessoas Vivendo com HIV: características relacionadas ao abandono do tratamento antirretroviral - Ziani, Jarbas da Silva (2024)
Introduction: four decades after the beginning of the human immunodeficiency virus epidemic, it is still known for its relevance on the world stage. However, with the advent of antiretroviral therapy, the human immunodeficiency virus became a chronic health condition with potential for control, an aspect that has been constantly decreasing the number of people who die as a result of AIDS, but falls short of elimination goals, especially in Brazil. Despite interventions to promote early diagnosis and treatment of HIV, hospitalization and mortality related to advanced HIV disease remain a Significant public health problem. Objectives: to relate the clinical and epidemiological profile of people living with HIV hospitalized with the abandonment of antiretroviral therapy. Method: retrospective cohort study of documentary nature, conducted with 219 people living with HIV who were hospitalized in a medium-sized hospital in the city of Santa Maria. A questionnaire prepared by the author of the study was used, and evaluated by expertise in the area. Pearson's Chi-Square and Fisher's Exact Test were used as a descriptive data analysis technique, in addition to multiple correspondence analysis. Results: of the 219 study participants, 98 (44.7%) abandoned treatment. The average of months of abandonment was 14.22 (SD± 8.04) and median of 12 months, with a minimum period of 5 months and a maximum of 47 months. Regarding the cloister analysis, it was identified that group two was associated with treatment abandonment and the worst prognoses, such as being male, black skin color, education level less than eight years of study and not having a fixed partnership. As for the clinical characteristics, it was alcoholic, high CV, CD4+ LT less than 200 cells/mm3 and a clinical picture compatible with AIDS. Also, regarding the relationship with the health system, they were diagnosed in the PHC, sought the service due to signs and symptoms, travel time greater than 31 minutes for the removal of the ART, had a previous history of treatment abandonment, registration of three or more ART regimens and had an association with the death outcome.Conclusion: finally, the study corroborates with the profile already known in the literature, signaling probable failure in the actions implemented in the long term and lack of new strategies for real impact on prevention, early detection and timely treatment, avoiding hospitalizations for this condition.